PENGARUH KECANGGIHAN TEKNOLOGI INFORMASI DAN KEMAMPUAN TEKNIK PEMAKAI SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA INDIVIDU PADA PT INDOMARCO PRISMATAMA CABANG BANJARMASIN - Ruslinda Agustina; Rara Gustiana; Amrina Ulimta Rosyada (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2021)
The research objective is to empirically prove the effect of system quality and information quality on user satisfaction of accounting information systems at PT Indomarco Prismatama Banjarmasin Branch. The method used in this study is a quantitative method by distributing questionnaires to 70 employees of PT Indomarco Prismatama Banjarmasin Branch who were used as respondents using SPSS Version 22.00 test equipment. Conclusion partially and simultaneously variables of information technology sophistication and technical ability of users of accounting information systems affect individual performance at PT Indomarco Prismatama Banjarmasin Branch